Sécurité foncière et gestion de la fertilite des sols: études de cas au Ghana et Bénin - Saidou, A.; Adjei-Nsiah, S.; Koussou, D.; Sakyi-Dawson, O.; Kuyper, T.W. (My University, 2007)
Within the framework of a larger research programme, Convergence of Sciences (CoS), studies were conducted on soil fertility management strategies in Ghana (Wenchi area) and Benin (Savè area). Soil fertility management in both areas includes short-term and longer-term practices. Both regions are characterised by the presence of natives and various groups of migrants that differ in their livelihood strategies. Natives and migrants enter into various tenure relationships. Driven by the increasing monetisation of the economy, such arrangements have evolved from land-for-labour relationships to a more monetary system,. In general natives claim that migrants are negatively affecting soil fertility through their cropping practices, while migrants claim that the nature of the tenure arrangement leads to insecurity and leaves them no choice but to mine the soil. There is, hence, widespread mistrust between natives and migrants, and the prospects for durable tenure arrangements that could maintain soil fertility seem limited. However, recognition of mutual interdependence could form a basis for the build-up of trust. In this study we highlight similarities and differences between the two areas in terms of livelihood strategies of migrants, soil fertility management practices and tenure arrangements. We also indicate the way in which alternative soil fertility management strategies could be effected under different tenure arrangements and describe the negotiation processes that have been started with a view to implementing such alternatives.
Keywords: land access; land policies; negotiation; soil degradation